Bioethics in a skeptical perspective: : how to not always treat trauma during exile and cultural displacement - Eliopoulos, Panos (Dia-noesis: A Journal of Philosophy, 2025)
In today’s world, bioethics seems to be the best solution we have in order to sustain a firm and efficient ethical understanding of our suffering world. However, in its good-willed narrative a lot is missing. Many of our fellow human beings carry another cultural and historical awareness than our own. In the context of interaction between the authority of the bioethicist and the needful person of exile or cultural displacement, trauma may indeed not get cured, or even worse, become deeper. As communication between distinct identities is indispensable, both doctor and patient need to re-identify themselves, often securing for each other a certain suspension of knowledge and moral decision.